Geographies of Urban Crime in Nashville, Tennessee, Portland, Oregon, and Tucson, Arizona, 1998-2002 - Cahill, Meagan Elizabeth ([Verlag nicht ermittelbar], 2006)
This research involved the exploration of how the geographies of different crimes intersect with the geographies of social, economic, and demographic characteristics in Nashville, Tennessee, Portland, Oregon, and Tucson, Arizona. Violent crime data were collected from all three cities for the years 1998 through 2002. The data were geo-coded and then aggregated to block groups and census tracts. The data include variables on 28 different crimes, numerous demographic variables taken from the 2000 Census, and several land use variables.